FNAC study of thyroid lesions using the Bethesda system - Dr. Mitali P. Dhamecha; Dr. Sunil Y. Swami; Dr. Arvind. G. Valand (Tropical Journal of Pathology and Microbiology, 2018)
Background: The most reliable, safe, cost-effective and accurate way to evaluate thyroid nodule is cytology, which has become the standard of care. As there is a 10% lifetime risk of developing a thyroid nodule, screening thyroid nodules had turned out to become a common medical problem affecting the general population. According to the guidelines of American association of clinical endocrinologists, fine needle aspiration cytology [FNAC] is the gold standard method available for distinguishing between benign and malignant thyroid swelling and is the most commonly performed non-gynaecological cytological procedure. Aims: To study the cytomorphological features and to classify cytologically the thyroid lesions based on the Bethesda system. Methods and Material: The present descriptive study was undertaken in a tertiary care hospital for a period of 3 years to analyse the role of FNAC in the diagnosis of thyroid lesions and classify them cytologically according to the Bethesda system. Results: 40 cases were classified as unsatisfactory, 328 cases as benign, 5 cases as AUS, 23 cases as FN/ HCN, 1 case as SFM and 3 cases as malignant.Out of 328 cases in benign category, 281cases belonged to BFN subcategory which was the most common non-neoplastic lesion of thyroid.The age range of patients presenting with the thyroid lesion was from 7-75 years. Maximum number of cases i.e. 116 were in the age group 31-40 years followed by 95 cases in the age group 21-30 years. Maximum cases in the benign category belonged to the age group of 31- 40 years. Maximum cases [10 out of 23 cases] in the follicular neoplasm category were seen in the age group ranging 21- 40 years. Out of 400 cases, females [359] cases outnumbered male [41] cases contributing 89.75% and 10.25% respectively with male to female ratio of 1:8.7. There was overall female preponderance seen in all diagnostic categories of TBSRTC. 5 cases diagnosed as AUS in our study were according to recommended criteria mentioned in Bethesda system i.e. less than 7%.One case each of PTC, MTC and UTC were seen in malignant category in our study. Conclusions: The Bethesda System for Reporting Thyroid Cytopathology (TBSRTC) helped to communicate interpretations of thyroid FNAC to referring physicians in terms that are short, concise and clinically helpful and it will also be a source of information for pathologists as well.